Treatment of chemotherapy-associated cardiomyopathy - Cai, Amanda W; Taylor, Marian H; Ramu, Bhavadharini (Current opinion in cardiology, 2019)
The number of cancer survivors is increasing, and cardiovascular events are a significant cause of morbidity and mortality in these patients. Preexisting cardiovascular conditions as well as the development of cancer therapeutics-related cardiac dysfunction (CTRCD), in particular left ventricular dysfunction and heart failure, limit the options for cancer therapies for these patients and contribute to reduced cancer survival. Recent guidelines and position statements from various cardiology and oncology societies provide an outline for the practicing physician for the management of CTRCD. However, this is largely based on data extrapolated from the general heart failure population (including patients without cancers) and is not based on strong evidence. There is now emerging evidence for the prevention and treatment of heart failure related to certain established chemotherapeutic drugs, whereas there is lack of trials for specific cardioprotective strategies to reduce cardiotoxicity of newer targeted cancer therapies. In this article, we discuss the most recent literature for the management of asymptomatic left ventricular dysfunction and heart failure related to chemotherapy, from prevention to the use of goal-directed medical therapies as well as discuss the role for advanced heart failure treatment in this population.